Assessment of Shared Socioeconomic Pathway (SSP) climate scenarios and its impacts on the Greater Accra Region - Siabi, E. K.; Awafo, E. A.; Kabo-bah, A. T.; Derkyi, N. S. A.; Akpoti, Komlavi; Mortey, E. M.; Yazdanie, M. (Elsevier, 2023)
The effects of climate change (CC) have intensified in Ghana, especially in the Greater Accra region over the last two decades. CC assessment under the new IPCC scenarios and consistent local station data is limited. Consequently, CC assessment is becoming difficult in data-scarce regions in Ghana. This study utilizes six different Regional Climate Models under the 6th IPCC Report’s Shared Socioeconomic Pathway scenarios (SSPs) of the CMIP6, which were bias-corrected with CMhyd over Greater Accra using ground station and PUGMF reanalysis data. The study reveals a reduction and potential shift in the intensity of precipitation in the region under the SSPs. Maximum temperature is expected to increase by 0.81–1.45 C, 0.84–1.54 C, 0.96–1.70 C and 0.98–1.73 C, while minimum temperature would likely increase by 1.33–2.02 C, 1.49–2.22 C, 1.71–4.75 C and 1.75–4.83 C under SSP1–2.6, SSP2–4.5, SSP3–7.0, and SSP5–8.5 scenarios, respectively. Thus, temperature will likely increase, especially at night in the near future. Rising temperatures and changes in precipitation have impacts on all strata of society, from agricultural production to power generation and beyond. These findings can help inform Ghanaian policymaking on Sustainable Development Goals 11 and 13 as well as nationally determined contributions within the Paris Agreement.